Pengaruh Lingkungan Kerja Fisik terhadap Stres Kerja Karyawan pada PT. Western Electric Sumbersible Pump Indonesia Assets 2 Field Ramba - Syafitri, Tasya Aulia (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Work stress is something that workers experience almost every day. Job stress can be defined as the pressure felt by employees because of work tasks that they cannot fulfill. Stress arises when employees are unable to meet job demands. Unclear job responsibilities, lack of time to complete tasks, lack of physical support to carry out work, conflicting tasks, and many other challenges make stress a factor that is almost impossible to avoid.This research aims to determine the effect of the physical work environment on work stress. This research is quantitative research with the sample in this study consisting of 41 employees of PT. West Indonesia Electric Source Pump. The data collection instrument is a questionnaire with a Likert Scale format consisting of five alternative answers. The results of the research show that the Physical Work Environment variable has a significant influence on Job Stress and the Physical Work Environment has an influence of 42.2% on the Job Stress of PT employees. West Indonesia Electric Source Pump.